Análisis Sedimentológico y geomorfológico de áreas lacustres en la Península Fildes, Isla Rey Jorge, Antártica Marítima - Vieira, Rosemary; Marotta, Humberto; Kellem da Rosa, Kátia; Jaña, Ricardo; Lorenz Simões, Carolina; de Souza Júnior, Enoil; Ferreira, Fabrício; Ronquette Santos, Liliane; Victor dos Santos, João; Aurélio Perroni, Marcos; Gonçalves, Matheus; Farias Santos, João Pedro; et al. (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 2015)
Geomorphological features and sedimentary characteristics are analized from five sets of shallow sediment cores collected in lakes in the Fildes Peninsula, King George Island. The geomorphology of the area was observed and sediments samples were obtained at field activities during the XXXI Brazilian Antarctic Operation (March-April/2013). Biogeochemical characteristics, physical parameters, mineralogical composition, particle size distribution, macroscopic characteristics of the sediments and satellite images were analized. Preliminary results indicate climatic and environmental changes in north-south transect of the peninsula. The mineralogical composition is associated with geological structure of the area, where basaltic rocks predominate. The particle size variation reflects different sediment source environments. Macroscopic analysis and mineralogical composition variation reflect the action of weathering along the peninsula. The sediments also have potential mineralization and subsequent release of greenhouse gases. A preliminary map of the classification of the lakes is presented. In addition, it was identified that wetland sediment presents methane production rates (CH4) about 40 times larger and more sensitive to the effect of global warming compared to lake sediment. Subpolar aquatic ecosystems sediments from Maritime Antarctica can be a preferential site for the effects of climate variability.